Case report: The intrauterine suture surgery—an original method in the treatment of old uterine false passage - Song, Xiaolei; Na, Re; Peng, Nianghai; Cao, Wenming; Ke, Yan; Liu, Ping; Chen, Chunlin (Frontiers in Surgery, 2023)
Aims and Objectiv To introduce an effective approach using the hysteroscopy system for patients with old uterine false passage of conservative treatment failed. Materials,Setting and Methods The image (Fig.1)description of the surgical procedures to demonstrate the detailed technique. The study was reviewed and approved by the institutional review board of Shenzhen Hospital of Integrated Traditional Chinese and Western Medicine.The patient, a 34-year-old woman, was treated in the department of gynecology of Shenzhen Integrated Traditional Chinese and Western Medicine Hospital in 2018 with the goal of "reducing menstrual volume by 2 years after abortion". Hysteroscopy was performed to make a clear diagnosis: 1. Uterine cavity adhesion 2. Old uterine false passage. After separation of adhesions, the patients were treated with estradiol and progesterone in sequence (estradiol valerate 3mg, bid, oral for 21 days, and dydrogesterone tablets 10mg, bid, oral for the second half of the cycle) for 3 months. After the review of hysteroscopy, the old false passages were found to be the same as before, so the patients were treated with suture and knotting under hysteroscopy to treat the old false passages of the uterus within 10 minutes, and the intraoperative blood loss was 2 mL. The patient was discharged 24 hours postoperatively without any adverse perioperative complications. Results After 2 months of operation, the review of hysteroscopy showed that the old false passages of the uterus disappeared. After half a year of follow-up, the menstrual volume increased compared with the previous one, close to the normal menstrual volume, No pain, menstrual discomfort, follow-up loss, contact again in 2022. In 2019, a baby boy was pregnant and delivered, now 3 years old, healthy. Conclusion: The Intrauterine suture surgery presents a clear visual ﬁeld to old uterine false passage of conservative treatment failed. In patients with old uterine false passage suffering from reduced fertility, The Intrauterine suture surgery can be a minimally invasive and effective alternative for old uterine false passage of conservative treatment failed.